2017
DOI: 10.1177/0748730417696787
|View full text |Cite
|
Sign up to set email alerts
|

Daily Light Exposure Patterns Reveal Phase and Period of the Human Circadian Clock

Abstract: Light is the most potent time cue that synchronizes (entrains) the circadian pacemaker to the 24-h solar cycle. This entrainment process is an interplay between an individual’s daily light perception and intrinsic pacemaker period under free-running conditions. Establishing individual estimates of circadian phase and period can be time-consuming. We show that circadian phase can be accurately predicted (SD = 1.1 h for dim light melatonin onset, DLMO) using 9 days of ambulatory light and activity data as an inp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 39 publications
3
83
0
Order By: Relevance
“…This line of investigation might eventually bear relevant insights for targeted treatment of humans who are facing frequent disruptions of their daily routines (e.g. shift work, traveling time zones, irregular lifestyles) or who have reduced exposure to natural light-dark cycles (Woelders et al, 2017).…”
Section: Phase Control Of Local Tissue Clocks By Non-scn Pacemakersmentioning
confidence: 99%
“…This line of investigation might eventually bear relevant insights for targeted treatment of humans who are facing frequent disruptions of their daily routines (e.g. shift work, traveling time zones, irregular lifestyles) or who have reduced exposure to natural light-dark cycles (Woelders et al, 2017).…”
Section: Phase Control Of Local Tissue Clocks By Non-scn Pacemakersmentioning
confidence: 99%
“…Therefore, it has been hypothesized that lighting conditions normally seen in an office, which involve constant intensity and color temperature, would make the rhythm vague [8]. In this study, the amplitude of rhythm was evaluated by temporal changes in rectal temperature during sleep; circadian phase advance due to daytime lighting conditions was assessed via dim light melatonin onset (DLMO); and sleep architecture was evaluated by PSG [2].…”
Section: Discussionmentioning
confidence: 99%
“…Dim light (<10 lux) has been standard procedure since the first FD experiment was performed in 13 . Apart from model calculations 15 , this is the first study we know that shows that short FD protocols can also be used for disentangling effects of bright light gated by wake duration related variation and circadian processes. During FD paradigms, concentrations of the nocturnal hormone melatonin have regularly been used as output measures of SCN rhythmicity.…”
Section: Interactive Effect During Daily Time Coursementioning
confidence: 99%
“…Earlier model simulations indicated that FD protocols with limited amount of cycles may typically overestimate circadian period at high light intensities 15 , and should therefore not be over-interpreted. Subjective alerting effects of light depend on homeostatic control.…”
Section: Interactive Effect During Daily Time Coursementioning
confidence: 99%
See 1 more Smart Citation